Determinan Peluang Investasi di Sektor Farmasi yang Terdaftar di BEI Periode 2015-2019 - Nike Dwi Kusuma Sudibyo; Maria Rio Rita (Jurnal Riset Akuntansi dan Keuangan, 2022)
This study analyzed how profitability, business activity and business life cycle affect investment opportunity set (IOS). The population included all manufacturing companies in the pharmaceutical sector listed on the Indonesia Stock Exchange (IDX) between 2015-2019 period, out of which 8 (eight) companies were sampled. Dummy regression analysis was performed usingSPSS software to analyze the data. The results indicated that this study stated that ROI had a positive and significant influence on MBVA. The contribution of independent variables to MBVA was 28.5 percent, and the remaining 71.5 percent were affected by variables that were not included in this study.